(untitled) (International journal of artificial intelligence, 2026)
This article highlights the importance of management competence for technical school directors. It presents practical and theoretical concepts for overcoming management and development problems in the educational process. The article contains detailed information about useful and necessary knowledge, skills, and abilities for leaders. We believe that this knowledge will be of great benefit in improving the educational process and its quality.